2017
DOI: 10.1186/s12889-017-4333-5
|View full text |Cite
|
Sign up to set email alerts
|

Restaurant-based intervention to facilitate healthy eating choices and the identification of allergenic foods at a family-oriented resort and a campground

Abstract: BackgroundRestaurant-based interventions can be an enjoyable way to encourage healthier eating choices by all members of a family. Thus, the principal aims of this study were a) to promote healthy diets by increasing healthy food offerings and b) to increase the number of foods offered specifically as gluten-free and lactose-free and to inform patrons by including nutritional and allergen information that complies with Regulation 1169/2011 regarding the food served in restaurants, takeaways and snack bars.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…These results are in line with other studies that tried to help restaurateurs better adapt their menus to the Mediterranean diet or healthier diets by giving personalized directions to restaurateurs regarding the dishes listed on their menus. Such instructions included introducing more side vegetables, offering fruit for dessert, and using extra virgin olive oil for different types of cooking (20,(28)(29)(30). Additionally, the pandemic resulted in some changes to customer preferences, and restaurateurs could be interested in acting on those changes, such as by offering more vegetarian/vegan or allergen-free dish choices.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with other studies that tried to help restaurateurs better adapt their menus to the Mediterranean diet or healthier diets by giving personalized directions to restaurateurs regarding the dishes listed on their menus. Such instructions included introducing more side vegetables, offering fruit for dessert, and using extra virgin olive oil for different types of cooking (20,(28)(29)(30). Additionally, the pandemic resulted in some changes to customer preferences, and restaurateurs could be interested in acting on those changes, such as by offering more vegetarian/vegan or allergen-free dish choices.…”
Section: Discussionmentioning
confidence: 99%
“…Greater consumers of livestock were more willing to try bivalves, suggesting there may be new opportunities to introduce key consumers to bivalve products. For example, professional chefs could develop high‐quality tasty bivalve recipes and test them in restaurants that serve livestock meats to encourage livestock consumers to try bivalves while minimizing the likelihood of off‐putting first experiences with bivalves (Tarro et al., 2017; Yoon et al., 2020). Our data also suggest that more heavily publicizing the health and environmental benefits of bivalves may make consumers more willing to substitute—this is a strategy that could be combined with the above initiatives by professional chefs.…”
Section: Discussionmentioning
confidence: 99%
“…As availability is an important prerequisite of purchasing and consumption of healthy food choices, comprehensive food policies targeting greater availability of healthy child menu items are needed. Previous studies [18,19] have shown that the availability of healthier food options in restaurants can be increased by adapting current menu items into healthier alternatives; increasing the number of fruit and vegetable options, especially in main dishes and desserts; and providing low-priced healthy options. Regular training of restaurant staff regarding healthy eating has also been shown to be a successful strategy for increasing the availability of healthy options on the menu [19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [18,19] have shown that the availability of healthier food options in restaurants can be increased by adapting current menu items into healthier alternatives; increasing the number of fruit and vegetable options, especially in main dishes and desserts; and providing low-priced healthy options. Regular training of restaurant staff regarding healthy eating has also been shown to be a successful strategy for increasing the availability of healthy options on the menu [19]. Studies have also found that changes to menus are possible without removing consumer choices or reducing revenue; affirming that such modifications have the potential to improve nutritional quality while allowing food outlets to remain competitive in the marketplace [18].…”
Section: Discussionmentioning
confidence: 99%